Primary medical care in Sri Lanka: hospital or general practice? - Varnam, Michael (1987)
A study was undertaken to compare aspects of patient care in private general practice and in a hospital emergency care clinic in Sri Lanka. General practitioners were found to spend more time with each patient, were more likely to write some kind of patient record and were more likely to carry out immunizations and investigations. They prescribed less and referred to specialists less than their colleagues in hospital primary care. In concluding that general practitioners in Sri Lanka provide an important part of primary care the 'orthodox' view that developing countries cannot afford this type of system is challenged.